Monkeypox Virus Outbreak 2022: Key Epidemiologic, Clinical, Diagnostic, and Prevention Considerations. (4th November 2022) - Kwong, Jeffrey; McNabb, Katherine C.; Voss, Joachim G.; Bergman, Alanna; McGee, Kara; Farley, Jason
Abstract: Monkeypox is a zoonotic infection that manifests as dermatologic lesions that may be painful or pruritic and can appear on the face, trunk, extremities, genitals, and mucosal surfaces. In 2022, cases of monkeypox increased exponentially and it was declared a public health emergency by the World Health Organization and the U.S. Department of Health and Human Services. Unlike previous monkeypox outbreaks, the current situation has disproportionately affected men who have sex with men and seems to be associated with lower mortality. Options for treatment and prevention are limited. The distribution and availability of vaccines and antivirals has posed challenges for patients, clinicians, and public health systems. Early recognition and management of persons with monkeypox is critical in controlling the spread of this infection. This article reviews key features of monkeypox and highlights current recommendations for clinical management, prevention, and considerations for persons with HIV. Implications for public health and nursing are discussed.